Inscriptions in Byzantium and Beyond Methods - Projects - Case Studies - Rhoby, Andreas (Verlag der Österreichischen Akademie der Wissenschaften, 2015)
The present book, the first collective volume entirely devoted to aspects of Byzantine epigraphy, mainly comprises papers delivered at two international meetings (Vienna 2010, Sofia 2011). The book is divided into four sections and includes contributions on the history of Byzantine epigraphy, on the definition of Byzantine inscriptions, on the methodoly of editing and on case studies of inscription of specific regions and eras.